PPPH-UAV: an open-source software to process raw GNSS data obtained from unmanned aerial vehicles for generating photogrammetric products - Bahadur, Berkay; Altuntas, Cemali; Demirel, Yasin; Ocalan, Taylan; Turk, Tarik (SPRINGER HEIDELBERG, 2026)
In recent years, the use of unmanned aerial vehicles (UAVs) for surveying applications, especially for photogrammetric product generation, has gained considerable interest. In addition to conventional methods, such as real-time kinematic (RTK) or post-processing kinematic (PPK) methods, the Precise Point Positioning (PPP) and its ambiguity resolution (PPP-AR) methods have been a serious alternative for the direct georeferencing of UAVs due to the ability to provide a high positioning accuracy with only a standalone GNSS receiver on a global scale. Taking the fact that no specialized software has yet been developed for the use of PPP/PPP-AR methods in UAV applications into account, this study presents an open-source software, namely PPPH-UAV, that can process the kinematic GNSS data from UAVs using PPP/PPP-AR methods. The software supports GPS, GLONASS, Galileo, and BeiDou observations to compute image projection center coordinates. The output file generated by the PPPH-UAV software can be input into the process of photogrammetric product generation. These distinctive features differentiate the software from existing ones by providing a user-friendly, easy-to-use way to process raw GNSS data from UAVs. This study also presents an experimental test which is performed to validate the PPPH-UAV software results with the CSRS-PPP online service, utilizing the PPK results as reference. The results demonstrate that positioning accuracies of 35.0 and 33.6 cm are acquired for the CSRS-PPP and PPPH-UAV results, respectively, which indicates that both solutions are comparable. The study concludes that the direct georeferencing in UAV applications can be conducted with PPP/PPP-AR solutions via the PPPH-UAV software.
Keywords: UAV; Direct georeferencing; PPP-AR; PPPH; Remote Sensing